2009
DOI: 10.1007/s00436-009-1609-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of larvicidal nature of fleshy fruit wall of Momordica charantia Linn. (family: cucurbitaceae) in the management of mosquitoes

Abstract: In view of the recently increased interest in developing plant-based insecticides as an alternative to chemical insecticides, this study was undertaken to assess the larvicidal potential of the various fruit wall extracts of Momordica charantia (cucurbitaceae) against two species of mosquito vectors, Anophels stephensi and Culex quinquefasciatus. Among the extracts tested, petroleum ether (LC(50) = 27.60; 17.22 ppm and 41.36; 15.62 ppm) extract was found more effective than carbon tetrachloride (LC(50) = 49.58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The alcoholic extract of C. procera (Asclepiadaceae) showed LC 50 values of 109.71 and 387.93 mg/L for A. stephensi and C. quinquefasciatus, respectively, and the LC 50 values were 13.06 and 86.47 mg/L, respectively, for latex of the plant (Shahi et al 2010). Maurya et al (2009) ). Wiesman and Chapagain (2006) reported that saponin extracted from the fruit of B. aegyptiaca showed 100% larvicidal activity against A. aegypti mosquito larvae.…”
Section: Discussionmentioning
confidence: 93%
“…The alcoholic extract of C. procera (Asclepiadaceae) showed LC 50 values of 109.71 and 387.93 mg/L for A. stephensi and C. quinquefasciatus, respectively, and the LC 50 values were 13.06 and 86.47 mg/L, respectively, for latex of the plant (Shahi et al 2010). Maurya et al (2009) ). Wiesman and Chapagain (2006) reported that saponin extracted from the fruit of B. aegyptiaca showed 100% larvicidal activity against A. aegypti mosquito larvae.…”
Section: Discussionmentioning
confidence: 93%
“…Bitter gourd fruit juice and hexane extract of bitter gourd fruit serves as a larvicide in mosquito larvae of Anopheles stephensi, Culex quinquefasciatus and Aedes aegypti (Singh, et al, 2006), likewise with petroleum ether extract, carbon tetrachloride extract and methanol extract of bitter gourd fruit. Those extracts were also capable of controlling larvae of A. stephensi and C. quinquefasciatus (Maurya, et al, 2009). Petroleum ether extract of bitter gourd fruit was more effective than the karbontertraklorida extract in controlling larvae of A. stephensi and C. quinquefasciatus.…”
Section: Introductionmentioning
confidence: 85%
“…LC 50 petroleum ether extract of bitter gourd fruit on the larvae of Anopheles stephensi was 27.60 ppm (treatment for 24 hours) and 17.22 ppm (treatment for 48 hours), and LC 90 petroleum ether extract of bitter gourd fruit on the larvae of Anopheles stephensi was 154.99 ppm and 94.79 ppm respectively for treatment 24 hours and 48 hours. While LC 50 of carbon tetrachloride extract of bitter gourd fruit for larvae of A. stephensi was 49.58 ppm (treatment for 24 hours) and 16.15 ppm (treatment for 48 hours), and LC 90 for the treatment of 24 and 48 hours also was 521.02 ppm and 369.99 ppm (Maurya, et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant is used as a vegetable as well as in traditional medicine throughout its range, most notably to treat diabetes, gastrointestinal problems, viral diseases, and for reproductive health [1][2][3][4][5] . Extracts of M. charantia fruit 6,7 and leaves 8 have shown mosquito larvicidal activities. In this work, we present the chemical composition of the leaf essential oil of M. charantia growing in Nigeria.…”
Section: Introductionmentioning
confidence: 99%